Intelligent Control Sytem for Car Muffler - Hendro Priyatman (Fakultas Teknik UM Pontianak, 2010)
Muffler is sub-system attached on car and used to control exhausting soundfrom machine. Conventional muffler using some material to filter exhaust. Withconventional muffler engine spends extra energy to push exhaust gasses trough thefilter. Of these, the filtering processes produce mechanical friction, and more energyconsumption. These condition decreased rehabilitee and performance from car.Active Noise Control (ANC) is sound field modification that can reduce or eliminateunwanted sound by electro-acoustical means. But ANC works best for sound fieldsthat spatially simple. Computational intelligent are interesting achievement atcontrol and computer theory. Some research is about neurofuzzy that has capabilityto control complicated system like sound field (produced by car machine).Combining ANC with neurofuzzy will attenuate noise as we desire.Key words: Noise, Control, Muffler, Neurofuzzy